The Profile of Sinonasal Tumors with Orbital Involvement in Dr. M. Djamil General Hospital, Padang, Indonesia: A 10-Year Overview - Pohan, Dwi Lestari; Ardizal Rahman; Mardijas Efendi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Sinonasal tumors are rare tumors, either malignant or benign, that vary greatly based on the origin and primary tumor location in the sinonasal tract. The close anatomical relationship between the sinonasal tract and the orbital cavity makes orbital involvement very common (50%-80%) in sinonasal tumors, and this indicates a negative prognostic factor in sinonasal malignancy. The purpose of this study is to demonstrate the profile of sinonasal tumors with orbital involvement in our center. Methods: Retrospective study from oncology subdivision files and medical records from January 2011 – December 2020. Collected data including age, gender, the clinical manifestations of orbital involvement, primary location, histopathology, and management of sinonasal tumors. Results: There were 35 patients examined by the oncology subdivision either directly came or consulted from the ENT department, consisting of 18 (51.4%) males and 17 (48.6%) females. The age of patients ranged from 11 to 83 years old. with the most common age groups being 41-50 and 51-60 (25.7% in each age group). The majority of the patients (77.1%) had presented with proptosis. Maxillary sinus was the most common (45.7%) primary site of tumors, and squamous cell carcinoma was the most common (51.4%) histopathology found. Most of the patients (37.1%) were treated with a combination of chemotherapy and radiotherapy. Conclusion: Orbital involvement commonly occurs in malignant sinonasal tumors with proptosis as a major clinical presentation. A combination of chemotherapy and radiotherapy was the most common practice management because the tumors were unresectable at the time of presentation.